Pharmacokinetics of asciminib in the presence of CYP3A or P‐gp inhibitors, CYP3A inducers, and acid‐reducing agents. Issue 7 (26th May 2022) - Hoch, Matthias; Huth, Felix; Sato, Masahiko; Sengupta, Tirtha; Quinlan, Michelle; Dodd, Stephanie; Kapoor, Shruti; Hourcade‐Potelleret, Florence
Abstract: Asciminib is a first‐in‐class inhibitor of BCR::ABL1, specifically targeting the ABL myristoyl pocket. Asciminib is a substrate of CYP3A4 and P‐glycoprotein (P‐gp) and possesses pH‐dependent solubility in aqueous solution. This report summarizes the results of two phase I studies in healthy subjects aimed at assessing the impact of CYP3A and P‐gp inhibitors, CYP3A inducers and acid‐reducing agents (ARAs) on the pharmacokinetics (PK) of asciminib (single dose of 40 mg). Asciminib exposure (area under the curve [AUC]) unexpectedly decreased by ~40% when administered concomitantly with the strong CYP3A inhibitor itraconazole oral solution, whereas maximum plasma concentration (Cmax ) decreased by ~50%. However, asciminib exposure was slightly increased in subjects receiving an itraconazole capsule (~3%) or clarithromycin (~35%), another strong CYP3A inhibitor. Macroflux studies showed that cyclodextrin (present in high quantities as excipient [40‐fold excess to itraconazole] in the oral solution formulation of itraconazole) decreased asciminib flux through a lipid membrane by ~80%. The AUC of asciminib was marginally decreased by concomitant administration with the strong CYP3A inducer rifampicin (by ~13–15%) and the strong P‐gp inhibitor quinidine (by ~13–16%). Concomitant administration of the ARA rabeprazole had little or no effect on asciminib AUC, with a 9% decrease in Cmax . The treatments were generally well tolerated. Taking into account the large therapeutic window of asciminib, the observed changes in asciminib PK following multiple doses of P‐gp, CYP3A inhibitors, CYP3A inducers, or ARAs are not considered to be clinically meaningful. Care should be exercised when administering asciminib concomitantly with cyclodextrin‐containing drug formulations.